The Effect of Cooperative Learning Model Using Snowball Throwing Type with Scientific Approach toward Students’ Learning Outcomes - Asni Johari, Risma Hesy Amrulia, Retni S. Budiarti, Ratna Sari Dewi (International Journal of Advanced Science and Technology, 2020)
The study seeks to analyze the effect of cooperative learning model using snowball throwing type with scientific approach toward students’ learning achievement in cognitive, affective and psychomotor aspects. The data are obtained from 62 students of PGRI 2 Senior High School in Jambi by using posttest to get the score of cognitive aspect, questionnaire to get the data of affective aspect and observation form to get the data of psychomotor aspect. The treatment that used in the study is cooperative learning model by using snowball throwing type with scientific approach in the learning process The result showed that cooperative learning model by using snowball throwing type with scientific approach has positive influence toward students’ learning outcomes in term of cognitive, affective and psychomotor aspects. The average score of posttest in cognitive aspect of experiment class is higher than the score of posttest in control class. The result of hypothesis testing showed that the value of tcount = 2,60 and value of ttable = 1,67 (tcount>ttable). Then, the average score of affective aspect in experiment class is also higher than control class, with the value of tcount = 6,9 and the value of ttable = 1,67 (tcount>ttable). Thus, it can be concluded that cooperative learning model by snowball throwing type with scientific approach is effective to improve students’ learning outcomes in term of cognitive, affective and psychomotor aspects. This learning model enable students to share their opinion individually or in groups, develop good characters of the students, involve the cognitive process that used to encourage students’ intellectual especially in high order thinking while they are identifying, understanding, and overcome the problem, and then apply them in the learning process. Furthermore, it makes the learning process focused on students’ centered. Thus, it will improve students’ critical thinking skills. It is recommended to the teachers to apply this model in learning activities in their class.